ANALISIS TERHADAP APLIKASI WHATSAPP DAN LINE MENGGUNAKAN METODE USABILITY DALAM TEKNOLOGI KOMUNIKASI - Rahimsyah, Meirynda Lastika; Hayati, Azmi Nurfauziah; Arapah, Rahmi Nurul (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
The mobile messenger application is a messaging application that is currently very often used by all humans to make communication easier and even a necessity for humans, because from this mobile messenger application we get information, namely the WhatsApp and LINE applications. In using the mobile messenger application, often some applications cannot use it efficiently and effectively, such as how to use it is too complicated, it becomes a consideration for users in using the mobile messenger application. This study aims to compare the two mobile messenger applications, namely the WhatsApp and LINE applications, assessed from their effectiveness and efficiency, as well as the interests of these mobile messenger users. And from the results of the research that we tried on 40 respondents using the questionnaire method that the WhatsApp mobile messenger has a high value compared to LINE with a total of 92% of respondents and the remaining 8% for the level of effectiveness and efficiency and from the level of most users all respondents use the Whatsapp application, 5 of them use the LINE application.